Thickness Control of Graphene Overlayer via Layer-by-Layer Growth on Graphene Templates by Chemical Vapor Deposition - Negishi, Ryota; Hirano, Hiroki; Ohno, Yasuhide; Haehashi, Kenzo; Matsumoto, Kazuhiko; Kobayashi, Yoshihiro (Japanese Journal of Applied Physics, 2011)
We examined graphene growth on graphene templates prepared by the mechanical exfoliation of graphite crystals using a sloped-temperature chemical vapor deposition (CVD) apparatus with ethanol. The structural characterization of the grown graphene layers in detail by atomic force microscopy and Raman spectroscopy reveals that the film thickening of graphene overlayers proceeds by the layer-by-layer growth mode, and that film thickness increases linearly as a function of growth time. This result indicates that a graphene growth technique using the CVD apparatus is a potential approach to precisely controlling the number of graphene layers, which is one of the important subjects for fabricating practical devices with uniform electrical properties using graphene as the channel material, such as field effect transistors.